Status Kesehatan Ayam Pedaging yang Diberi Limbah Kulit Buah Naga (Hylocereus Undatus) dalam Air Minum Sebagai Antioksidan - Sadarman Sadarman (Kutubkhanah, 2013)
This study aimed to obtain information about the health status of broilers fed dragon fruit peel waste (Hylocereus undatus) in drinking water as an antioxidant. Commercial broiler strain Cobb 100 birds as much as one day of age used in this study, which were divided into 4 treatment. Each treatment was repeated 5 times, each repeat totaled 5 chickens, the chickens were only given fresh drinking water (T1), chicken skin dragon fruit was given 17.75 g/5 ml/tail (T2), chickens fed dragon fruit peel 35.50 g/5 ml/tail (T3), and chicken skin dragon fruit was given 53.25 g/5 ml/tail (T4). Blood samples were taken on the fourth week, to see the number of erythrocytes, hemoglobin, and leukocyte hematokcrit values and antibody titers. The results showed that administration of dragon fruit peel extract as an antioxidant in the drinking water showed erythrocytes, hemoglobin and hematocrit values of broiler chickens is still within the normal range with it leuckosit increased sharply. However, granting dragon fruit peel extract in drinking water such as antioxidants can improve